NowościExpanding the indication for stent-grafting in thoracic aortic aneurysms - Garlicki, Mirosław; Nowicki, Mirosław; Walecki, Jerzy; Łabuś, Krzysztof; Ehrlich, Marek; Czub, Paweł; Gil, Robert (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: Thoracic aortic aneurysms are life-threatening and continue to challenge surgeons. In recent years, transluminally placed endovascular stent-grafts have been used for a variety of descending aortic pathological conditions. Material and methods: We report herein on two cases of thoracic aortic pathologies that have been treated with a combined surgical and endovascular procedure. The first case deals with a 71-year-old man who was admitted for severe chest pain 3 weeks after off-pump triple coronary bypass grafting. CT revealed a dissection in the ascending aorta. The second case involves a 74-year-old patient with an aortic arch aneurysm 7 cm in diameter. Annually performed CT scans revealed a rapid progression of the aneurysm with a growth rate of over 1 cm in the last year. Besides his age, the patient had significant comorbidities Results: Both cases were treated successfully with stent-grafts. In the first case, the stent was introduced through a Dacron-graft and deployed under transesophageal echocardiography (TEE) control in the ascending aorta, right above the two proximal vein anastomoses. This led to the reapproximation of the intimal and medial layer. Blood flow to the bypass veins was unaffected and flow in the false lumen could be stopped as confirmed by TEE. The second case had a double transposition of the great arteries before the stent-graft intervention and a stent-graft was inserted into the aortic arch and deployed overstenting the left subclavian artery. The post procedural performed angio showed no sign of endoleak. Conclusion: Stent-graft placement is a viable option in highly selected patients with aortic aneurysms or dissections.